Response of intercrops and nutrient management on the performance of tobacco based intercropping system and assessment of system sustainability (Bangladesh Journal of Botany, 2014)
Intercropping of tobacco with garlic produced the highest total (2292 kg/ha) and first grade (1256 kg/ha) cured leaves of tobacco. In the recommended dose of respective intercrops 75% produced total and first grade cured tobacco leaves compared to 100 per cent of the recommended dose. Tobacco quality was also influenced with nutrient management. Puckering and maturity scores did not impaired up to 50 per cent application of nutrients to intercrops. Among the intercrops garlic gave the highest economic yield (1.18 t/ha) over three years on the basis of monetary gain. The highest net return (Rs 47,948 / ha) and cost benefit ratio (1:1.78) was achieved under tobacco + garlic intercropping system. Nutrient supplied at 75 percent of recommended dose provided net return (Rs 45551/ ha) and cost benefit ratio (1:1.81) equivalent to 100 per cent of recommended doses. Soil fertility was either maintained or improved due to intercropping intervention in comparison to cultivating tobacco sole. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18040 Bangladesh J. Bot. 42(2): 343-348, 2013 (December)